Case report on antipsychotic induced catatonia in an incarcerated patient - Nguyen, Han; Cannell, Ruslana; Rollakanti, Suman; Rosenthal, Johanna; Seigler, David (Frontiers in Psychiatry, 2023)
Antipsychotic-induced catatonia is an iatrogenic and debilitating adverse reaction, but there is a dearth of recent documented cases. This report describes a 35-year-old incarcerated Korean-American male with a history of unspecified psychosis who presented for antipsychotic induced catatonia after administration of haloperidol decanoate intramuscular (200mg across the span of one week). Neurologic workup was performed including MRI, lumbar puncture, and electroencephalography. Despite an approximate month long hospitalization, benzodiazepine challenge, benztropine trial, and amantadine adjunct, our patient continued to experience bradykinesia, waxy flexibility, mask-like facies, and was minimally verbally responsive. Several challenges in the treatment of incarcerated individuals at the hospital are highlighted in this case report, including adverse reaction to medication, difficulty of care coordination, and limited access to health records among providers.Rating Scale (BFCRS) can provide systematic scoring to quantify severity of catatonia. 3,4 The BFCRS is based on 23 examination items; criteria for catatonia is met when two or more of the first 14 items are positive. Higher BFCRS scores indicate either more numerous symptoms or higher severity of symptoms. Mutism, stupor, staring, posturing, and negativism are some of the features of catatonia in this widely used scale. 3 Catatonia is most associated with psychiatric conditions, but can also occur as a result of neurologic traumas, autoimmune diseases, metabolic disorders, and medication exposure (e.g., antipsychotics), and more. 4 Iatrogenic movement disorders that occur after administration of antipsychotics are termed antipsychotic induced Deleted: neuroleptic 36 Deleted: neuroleptic 37 Deleted: haldol 38 Commented [HN1]: Reviewer 2 edits in red text using Track changes Reviewer 4 edits in yellow highlight Deleted: Neuroleptic 39 Deleted: (NIC)